Diagrams of power in Benjamin and Foucault the recluse of architecture - Jackson, Mark (Springer, 2022)
This book's overarching premise is that discussion and critique in the discourses of architecture and urbanism have their primary focus on engagements with form, particularly in the sense of the question as to what planning and architecture signify with respect to the forms they take, and how their meanings or content (what is "contained") is considered in relation to form-as-container. While significant critical work in these disciplines has been published over the past 20 years that engages pertinently with the writings of Walter Benjamin and Michel Foucault, there has been no address to the co-incidence in the work of Benjamin and Foucault of an architectural figure that is pivotal to each of their discussions of the emergence of modernity: The arcade for Benjamin and the panoptic prison for Foucault have a parallel role. In Foucault's terms, panopticism is a "diagram of power." The parallel, for Benjamin, would be his understanding of "constellation." In more recent architectural writings, the notion of the diagram has emerged as a key motif. Yet, and in as much as it supposedly relates to aspects of the work of Foucault, along with Gilles Deleuze, this notion of "diagram" amounts, for the most part, to a thinly veiled reinstatement of geometry-as-idea. This book redresses the emphasis given to form within the cultural philosophy of modernity and--particularly with respect to architecture and urbanism--inflects on the agency of force that opens a reading of their productive capacities as technologies of power. It is relevant to students and scholars in poststructuralist critical theory, architecture, and urban studies.
Keywords: Benjamin, Walter -- 1892-1940; Foucault, Michel -- 1926-1984; Urbanität; Form -- Philosophie; Architektur; Architecture / Philosophy; Power (Philosophy); Benjamin, Walter / 1892-1940 / https://isni.org/isni/0000000121010732; Foucault, Michel / 1926-1984 / https://isni.org/isni/000000012146278X; Benjamin, Walter / 1892-1940; Foucault, Michel / 1926-1984